2013
DOI: 10.1016/j.bjane.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The growth of bacteria in infusion drugs: propofol 2% supports growth when remifentanil and pantoprazole do not

Abstract: Propofol strongly supports the growth of the microorganisms tested, although remifentanil and pantoprazole do not. Therefore, it is important to follow the strict aseptic techniques for the preparation of propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…10 Remifentanil, which is an analog of fentanyl, was also stated to decrease bacterial growth. 16,17 Tamai-Shacooriz et al in their investigation, reported that sufentanil increased the antibacterial activity of bupivacaine but not ropivacaine. 9 Antibacterial effect of lidocaine was shown in several investigations.…”
Section: Discussionmentioning
confidence: 98%
“…10 Remifentanil, which is an analog of fentanyl, was also stated to decrease bacterial growth. 16,17 Tamai-Shacooriz et al in their investigation, reported that sufentanil increased the antibacterial activity of bupivacaine but not ropivacaine. 9 Antibacterial effect of lidocaine was shown in several investigations.…”
Section: Discussionmentioning
confidence: 98%
“…Plaques were incubated at 36 ± 2 °C for 24 h. Colony numbers (CFU.mL −1 ) were measured by a second researcher. 16 , 17 …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have concluded that while simultaneous infusion removed the ability to selectively control the use of each drug, it resulted in decreased incidences of procedural respiratory depression and patient recovery time [18,19]. Furthermore, when mixed with propofol, remifentanil has been found to inhibit the bacterial growth that readily occurs within the lipid emulsion, possibly due to its glycine excipient and low pH [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For mixtures of remifentanil and propofol specifically, there are a lack of studies investigating a variety of remifentanil concentrations, the impact of mixing on both remifentanil and propofol concentration, and how manipulating solution pH (through the use of different remifentanil reconstitution mediums) affects the stability of the mixture. pH is of particular importance for a combination of remifentanil and propofol as remifentanil is believed to undergo rapid hydrolysis when exposed to a pH range of 7-7.5 [21]. After reconstitution with water, remifentanil has a pH of 3.0 [24].…”
Section: Introductionmentioning
confidence: 99%